Electrocatalytic Oxidation of Carbohydrates Mediated by Nitroxyl Radical‐modified Electrodes in Aqueous Solution. Issue 1 (16th November 2017) - Ono, Tetsuya; Sato, Katsuhiko; Shimizu, Syunki; Yoshida, Kentaro; Dairaku, Takenori; Suzuki, Yasuhiro; Kashiwagi, Yoshitomo
Abstract: The electrocatalytic activity of a 2, 2, 6, 6‐tetramethylpipridine‐ N ‐oxyl (TEMPO)‐modified electrode toward the oxidation of carbohydrates in phosphate buffer solution was investigated under neutral aqueous solution conditions at 25 °C. The modified electrode was prepared on the surface of a glassy carbon electrode by the electrochemical polymerization of a TEMPO precursor containing a pyrrole side chain. Cyclic voltammetric studies showed that the anodic peak current increased with the concentration of carbohydrates in a dose‐dependent manner. Abstract :